Prevalence of hormone-related mood disorder symptoms in women with ADHD. (January 2021) - Dorani, Farangis; Bijlenga, Denise; Beekman, Aartjan T.F.; van Someren, Eus J.W.; Kooij, J.J. Sandra
Abstract: This is the first study to assess the prevalence of symptoms of premenstrual dysphoric disorder (PMDD), episodes of postpartum depression symptoms (PPD) after first childbirth, and climacteric mood symptoms in Attention-Deficit/Hyperactivity Disorder (ADHD). 209 consecutive women (18–71 years) with ADHD completed the PMDD chapter of the Neuropsychiatric Interview Plus version 5.0.0 to assess PMDD, the Edinburgh Postnatal Depression Scale to assess PPD, and the Greene Climacteric Scale to assess climacteric symptoms. Comorbid psychiatric disorders, medication use, and chronobiological sleep characteristics were also assessed. The prevalence of PMDD and PPD were high in ADHD, compared to the general population. PMDD symptoms were associated with less use of contraceptives. Antidepressants were associated with more PMDD symptoms. The following GCS scores were significant increased: anxiety, depression, and sexual dysfunction, vasomotor and somatic complaints. No significant differences were found in sleep characteristics or current comorbidity between the groups with and without PPD or PMDD, or increased climacteric scores. The prevalences of PMDD, PPD and climacteric scores were high in women with ADHD. This is the first study in women with ADHD that suggests that female ADHD patients suffer from significant PMDD symptoms, experience PPD during the first child birth, and experience more severe climacteric symptoms.